2017
DOI: 10.1016/j.jpainsymman.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

“I Just Felt Like I Was Stuck in the Middle”: Physician Assistants' Experiences Communicating With Terminally Ill Patients and Their Families in the Acute Care Setting

Abstract: Context Terminally ill hospitalized patients and their families consistently rank effective communication and shared decision-making among their top priorities. Advance Practice Providers such as Physician Assistants (PAs) are increasingly providing care in the hospital setting and are often called to communicate with patients and families. A first step to improving PA communication is to better understand PAs’ current experiences in their daily practices. Objectives This study aimed to explore: 1) roles PAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Studies discussing research gaps under the clinical theme comprised 56% of all papers found ( n = 14) [ 12 , 15 , 17 21 , 23 , 26 , 27 , 30 , 31 , 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies discussing research gaps under the clinical theme comprised 56% of all papers found ( n = 14) [ 12 , 15 , 17 21 , 23 , 26 , 27 , 30 , 31 , 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another gap in the clinical elements of HPC/EoL pertains to the subtheme of overall training and education that healthcare providers and palliative healthcare providers received (32%, n = 8) [ 12 , 15 , 18 20 , 23 , 27 , 35 ]. For example, five studies reported that healthcare providers expressed uncertainty in communicating with patients as they experienced gaps in knowledge, skills, and training [ 12 , 15 , 18 , 31 , 35 ]. As well, there were differences in the amount of HPC training each healthcare provider received, with some having more knowledge on end-of-life issues than others [ 15 , 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations